EVALUASI IMPLEMENTASI KEBIJAKAN PROGRAM INDONESIA PINTAR PADA SMA NEGERI 11 SERAM KABUPATEN SERAM BAGIAN TIMUR PROVINSI MALUKU - Kuspriyanto, Moch. (MAP (Jurnal Manajemen dan Administrasi Publik), 2024)
The aim of this research was designed to describe the implementation of the Indonesia Pintar program at SMA Negeri 11 Seram Timur, analyzing the supporting factors for the Indonesia Pintar Program at SMA Negeri 11 Seram Timur Regency, East Seram, Maluku Province. This study used descriptive qualitative method. The results of the research regarding Determination of KIP Acceptance, Distribution of PIP, Notification and Submission of Decision Letters, Account Activation and Withdrawal of Funds and Cancellation of KIP were carried out smoothly by SMA Negeri 11 Seram Timur, even though the geographical location of the school made the process of collecting PIP funding assistance late.